Morphology and multigene phylogeny reveals five new species of Hydnaceae (Cantharellales, Basidiomycota) from China - Qian Zhou; Chengbin Qian; Chuyun Zhang; Qidong Su; Yiliang Li; Shihui Zhang; Nian Mu; Taimin Xu; Hongmin Zhou; Changlin Zhao (MycoKeys)
Wood-inhabiting fungi play a fundamental role in ecosystem processes, particularly in wood degradation and the recycling of organic matter. In this study, a new genus, Clavuliella gen. nov., and five new species, viz. Burgella albofarinacea sp. nov., B. fissurata sp. nov., Burgoa wumengshanensis sp. nov., Clavuliella sinensis sp. nov., and Sistotrema sinense sp. nov., are described from China and illustrated based on morphological characteristics and molecular phylogenetic analyses. Sequences of the ITS+nLSU genes were used for the phylogenetic analyses using Maximum Likelihood, Maximum Parsimony, and Bayesian Inference methods. The phylogram of the family Hydnaceae, based on the ITS+nLSU rDNA gene regions, included four genera; Burgella, Burgoa, Clavuliella and Sistotrema. The topology based on these sequences revealed that Burgella albofarinacea was closely related to B. flavoparmeliae, and B. fissurata was grouped with B. lutea. The taxon Burgoa wumengshanensis was sister to the clade that included B. anomala and B. verzuoliana. The species Sistotrema sinense was grouped closely with S. brinkmannii and S. farinaceum. All new taxa can be readily recognized by their macroscopic and anatomical characteristics. The five new species, closely related taxa in the phylogenetic tree, and morphologically similar species are discussed.